NOWY KSZTAŁT NAUCZANIA MORALNEGO PAPIEŻA FRANCISZKA A INTUICJE ZAWARTE W TEOLOGII KS. PROF. STANISŁAWA OLEJNIKA - SKOBEL, STANISŁAW (Studia Theologica Varsaviensia, 2016)
Moral Theology of F. prof. Stanislaus Olejnik inscribed permanently into the achievements of Polish moralizing. Although much has already been created years ago, it turns out to be very current today. This is evident in comparison with the pontificate of Pope Francis and his method of teaching morality.. Scientific intuitions of this famous Polish moralist may be an inspiration for the work of contemporary researchers. Especially clearly this can be seen in terms of a new approach to methods of teaching about morality, at the level of social morality and spirituality as a practice of the moral life. Let the many Polish moralists, following the example of his teachers, they develop his insights and make it more current